A Study of the Changes in the Permeability of the Sintering Bed in the Imperial Smelting Process - K. Kawanaka; Y. Mori (The Minerals, Metals and Materials Society, 2000)
The permeability changes during the sintering of the feed for the Imperial Smelting Process (ISP) were investigated using an experimental sintering pot, as well as with a mathematical model. The results obtained were as follows. The blowing resistance in the sintering bed changes as the sintering reaction proceeds. It increases at the beginning of the reaction when the temperature of the bed is still low. Then it decreases as the reaction continues, accompanied by an increase of the bed temperature. The increase of the blowing resistance in the bed during the sintering process mainly occurred in the drying zone, and was comparatively small in the reaction and cooling zones. Based on Erugen's equation, the change of the permeability during sintering is explained by the decrease of the apparent fractional void volume in the drying zone of the bed.